Effects of Exogenous Gibberellin on Seed Germination and Seedling Growth of Passion Fruit Under Salt Stress - Jinqiang SU; Xiaoqing XIE; Qiujin LIN; Tianxiang ZHANG (Guangdong nongye kexue, 2023)
【Objective】The effects of exogenous gibberellin on seed germination and seedling growth of passion fruit under salt stress were studied.【Method】Different concentrations (50, 100, 150 mg/L) of NaCl solution were used to simulate salt stress, and different concentrations of gibberellin were used for seed soaking treatment (50, 100 mmol/L) and foliar spraying treatment (25, 50 mmol/L) of passion fruit. The physiological regulation effects of exogenous gibberellin on passion fruit under salt stress was analyzed by measuring the germination and physiological indexes of the seeds, as well as the growth and physiological indexes of the seedlings.【Result】Under 150 mg/L NaCl stress, 50 mmol/L gibberellin soaking treatment could increase the germination rate and germination index of passion fruit seeds by 20.4% and 16.3%, respectively. It promoted the increase of embryo length and radicle length of passion fruit by 7.9% and 20.5%, respectively. At the same time, the MDA content decreased by 10.8%, the soluble protein content, SOD activity and POD activity increased by 5.5%, 21.3% and 28.5%, respectively. After spraying 25 mmol/L gibberellin on the leaves under 150 mg/L NaCl stress, the number of leaves, plant height, root length and stem diameter of passion fruit seedlings increased by 16.3%, 20.3%, 20.9% and 19.4%, respectively; furthermore, the chlorophyll content of leaves, soluble protein content, SOD activity and POD activity of the seedlings increased by 13.0%, 26.2%, 12.0% and 9.3%, respectively.【Conclusion】The seed soaking treatment with gibberellin solution could significantly promote the germination of passion fruit seeds under salt stress, and had a significant alleviating effect on the inhibition of embryo and radicle growth. Foliar spraying gibberellin could significantly alleviate the effects of 100 and 150 mg/L salt stress on the growth of passion fruit seedlings, especially for 150 mg/L salt stress seedlings.